Enhancing energy-efficient home appliance adoption: Media publicity strategies and planned behavior theory - Andika, Andika; Fadhilah, Muinah; Luthfiana, Della Nanda; Nadia, Nadia; Amirullah, Malik Abd Karim (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
Adopting energy-efficient home appliances is one of the critical strategies for supporting environmental protection through reducing energy consumption. This study aims to identify factors contributing to consumers’ intentions to adopt energy-efficient household appliances (EEHA) in Indonesia, particularly in Java, a representative area of energy consumption in the country. Adopting the Theory of Planned Behavior (TPB) as the main theoretical framework, the study expands the model to include media publicity (MP) variables as external factors. The survey method was applied to 200 respondents, and the collected data were analyzed using the Structural Equation Modeling (SEM) technique through Smart-PLS 4. The results revealed that consumer attitudes (CA), perceived behavioral control (PBC), and subjective norms (SN) significantly affected consumers’ intentions in adopting EEHA. Furthermore, the study found that MP significantly influences CA. Likewise, as we expected, MP significantly affected PBC and SN, marking the first time this relationship has been identified in the context of the adoption of EEHA. Based on these findings, we discuss some of the implications for policymakers, marketers, and environmental practitioners in promoting the adoption of EEHA to accelerate the transition to more sustainable energy consumption in households.